INCLUSION: A QUESTION FOR THE EXERCISE OF THE CITIZENSHIP (Fiep Bulletin - online, 2013)
This study has the purpose of making the reflection about social inclusion, specially in those people with special needs in the school environment. Also it intends to point out the importance of the access and permanence of the same ones in regular education, in a perspective of integration and socialization, based on discussions and excellent and important documents. On the other hand, it tells - based in innumerable occurrences - to the lack of more consistent, systemic and permanent actions, besides the necessity of the implantation of more great political inclusive that make better learning possible , and that it offers in fact equality chances for all. In this dimension, it seems to be reserved to the professional of Physical Education, the mission of trying to develop, through activities multi and trans-disciplinaries, through disciplines, the formation of a most integral the human being, having as his objective the promotion and exercise of the citizenship.
Keywords: Physical Education; Children; Multi and Transdiscliplinaire